Information dissemination at banking institutions in Temerloh and Mentakab: a case study / Mas Anom Abdul Rashid ... [et al.] - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman; Che Omar, Nurhedayah; Ismail, Nurizate (2008)
The main objectives of this study are to analyze the methods of information dissemination between employees and employers, identifying the barriers to information dissemination and determine the consequences of information dissemination failure in banking institutions. A total of 34 questionnaires were mailed to individual members of CIMB Bank, RHB Bank and AM Bank and only 27 individuals responded. The main focus of the research is to see the effectiveness in information dissemination process in relation to change. The type of this research is descriptive research. This research analyzes the information dissemination phenomenon. Results indicate that the effective methods to disseminate information are using electronic mail and using other electronic media such as CD-ROMs and web pages. The rapidly changing scenario in banking institutions requires the information dissemination in relation to change to be managed in an effective way. The effectiveness of information dissemination will influence the way employees take action whether to immediately respond to the information they receive or delay the response. Besides, it is found that there are several barriers and consequences that occur during the information dissemination process. This paper presents in detail the factors that exist in information dissemination process, namely new knowledge, leadership style, strategies, attitude and barriers. The final part of this research provides conclusion and recommendations based on the findings.